Synthetic bakuchiol derivatives: ester and ether analogs with activity against clinically important bacteria - Valdés, Francisca; Muñoz, Evelyn; Martinez, Manuel; Ferreira, Catalina; Silva, Valentina; Madrid, Alejandro; Díaz, Katy; Villarroel, Constanza; Montenegro, Iván (Frontiers in Pharmacology, 2025)
IntroductionWith the rise of antibiotic resistance and healthcare-associated infections, there is a growing need for alternative therapies. Otholobium glandulosum (L.) J.W. Grimes (= Psoralea glandulosa L.) (Fabaceae) and its active compound, bakuchiol, have demonstrated significant antimicrobial and biological potential. This study investigates bakuchiol-based synthetic derivatives as promising antibacterial agents against clinically relevant pathogens.MethodsFrom the aerial parts of O. glandulosum, a resinous exudate was obtained, from which bakuchiol was isolated. This compound was used as a precursor to synthesize a series of ester-type (4–8) and ether-type (9–15) derivatives. All compounds were purified, their structures were confirmed by nuclear magnetic resonance (NMR), and they were evaluated in vitro for antibacterial activity against Gram-positive and Gram-negative strains. The most active derivatives were further tested in live/dead assays, and their pharmacokinetic and toxicity profiles were predicted in silico using the SwissADME and ADMETlab servers.ResultsThe ester derivatives exhibited bactericidal activity against Staphylococcus aureus and Streptococcus agalactiae, with compounds 4 and 5 being particularly effective, causing 90% growth inhibition. Compound 6 displayed a minimum inhibitory concentration (MIC) of 320 μg/mL against Pseudomonas aeruginosa. However, none of the compounds showed bactericidal activity against Escherichia coli. A structure–activity relationship (SAR) analysis indicated that chain length, lipophilicity, and stereochemistry influenced both efficacy and bacterial selectivity. In silico assays indicated acceptable absorption, low mutagenicity, and moderate hepatotoxicity, with limitations related to high LogP values.ConclusionThese results support the potential of bakuchiol ester-type derivatives as antibacterial agents, which encourages future in vivo studies and synthetic optimization.